Encouraging children to read - Macaranas, Julia Antoinette D. (2013)
Reading is a skill that gives the individual countless benefits. One of these benefits are that children who like to read are shown to be more equipped in handling intellectual and emotional development as they are growing up. However, not many children like to read. Encouraging children to read, then is a necessary course of action for parents and those responsible for the wellbeing and development who wish to equip their child with the arsenal to handle many events. Anticipated pleasure from reading encourages children to read more. Feeling pleasure in aesthetic beauty by assimilating illustrations and text is aimed output of this study. Initially, creation of a webcomic was the anticipated output, however, the study have shown that picture books would be better for children, aged seven to twelve years old, living in Metro Manila.